Effect of extrusion temperature in the mixture of tarwi flours (Lupinus mutabilis) and rice Orysa sativa) for the production of a Snack - Aranda Tarazona, Jair Jol (2021)
The grains of tarwi (Lupinus mutabilis S.) have a high protein content, and are also very rich in some essential amino acids, such as lysine. However, the extrusion parameters significantly affect the protein contents of the generated products. The main objective of the study was to determine the best extrusion temperature in a snack made from tarwi and rice flours. For the production of the snack, tarwi flour (Lupinus mutabilis Sweet) was used, in three concentrations (8, 10 and 12%) and three proportions of rice flour (Orysa sativa) (88, 90 and 92%). The extrusion parameters were: extrusion temperature (100, 110, 115) ° C, screw rotation speed 1560 rpm, feed speed 1kg / min, blade speed 630 rpm, water flow 19.5 ml / min and diameter of the outlet nozzle 0.6 mm. A multilevel factorial design was used, achieving 9 experimental runs. The results of the sensory and proximal chemical analysis determined that the best snack formulation was obtained with 90% of the rice content and 10% of the tarwi content; furthermore, it was determined that the extrusion temperature was 110 ° C. The prepared snack resulted in a protein content of 13.11%, 4.03% fiber and its shelf life was 25 days; resulting in a product with high protein content, high organoleptic acceptance and suitable for consumption.